Market Orientation and Sharia Product Knowledge on Business Performance: Innovation Capability as an Intervening Variable in Sharia Banking Industry - Irfan Rahmana, MA; Avianda Nurcahyo, Satria; Pranaditya, Ari (Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Purpose - This study investigates the influence of market orientation and Sharia product knowledge on business performance in the Sharia banking industry, with innovation capability as an intervening variable. Method - Quantitative approach, the research employs Structural Equation Modeling Partial Least Squares (SEM PLS) to analyze data collected from a saturated sample of 213 permanent employees of PT Bank Muamalat, Central Java Regional Office. Result - The findings reveal that both market orientation and Sharia product knowledge significantly and positively impact business performance. Furthermore, innovation capability also demonstrates a positive and significant effect on business performance. The results confirm that innovation capability effectively serves as an intervening variable, strengthening the relationship between market orientation, Sharia product knowledge, and business performance. All five hypotheses tested in the study were supported, indicating the critical role of market orientation and Sharia product knowledge in enhancing innovation capability, which in turn improves business performance in the Sharia banking sector. Implication - These findings highlight the importance of aligning market strategies with Sharia principles and leveraging innovation to achieve competitive advantages in the dynamic banking industry. Originality - This research contributes to the growing literature on Sharia banking by providing empirical evidence of the interplay between market orientation, Sharia product knowledge, and innovation capability. It underscores the necessity for Sharia banks to prioritize knowledge dissemination and innovative practices to sustain performance in a competitive market. Future research is recommended to explore other potential variables that may mediate or moderate these relationships. Keywords: Market Orientation, Sharia Product Knowledge, Business Performance, Innovation Capability, Sharia Banking